Strategy for Strengthening Character Based on Local Wisdom as a Foundation for Facing the 5.0 Era - Nurdiansyah, Edwin; Sapriya, Sapriya; Darmawan, Cecep; Abdulkarim, Aim; Kurniawan, Dedi (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2025)
The tendency of citizens in developing countries such as Indonesia to adopt modern foreign nations as social role models has contributed to the marginalization of Indonesia’s own cultural identity. The Pancasila-based character, enriched with local wisdom, represents a distinctive national strength. This study aims to analyze the manifestation of Society 5.0 within the scope of Indonesian education, identify strategies to strengthen Pancasila character in this context, and formulate strategic plans for character formation rooted in local wisdom. This study employs qualitative methods, synthesizing data from scientific books, peer-reviewed journals, and official government documents to capture the latest trends and best practices of the Society 5.0 era, which provide important opportunities to strengthen national character. Findings indicate that the Society 5.0 era offers a pivotal opportunity to reinforce national character. Character education, anchored in local wisdom and aligned with Pancasila values, strengthens Indonesia’s national identity and can be effectively implemented through a comprehensive management approach that encompasses intra-curricular, co-curricular, and extracurricular activities. This research provides a practical framework for character-education management that can inform policy decisions and educational practice, offering a scalable model for embedding Pancasila values into future-oriented education systems.